Ratio-of-distance rigidity theory with application to similar formation control - Cao, Kun (2021)
This paper develops a ratio-of-distance (RoD) rigidity theory to study when a framework can be uniquely determined by a set of RoD constraints up to similar transformations (translation, rotation, scaling, and reflection). In particular, a framework is specified by a set of RoD constraints (the RoD of a pair of edges joining a common vertex) instead of distance, bearing, and angle constraints assumed in existing literature. Its relations to three existing rigidity theories (distance, bearing, and angle rigidity theories) are established. The proposed RoD rigidity theory is further applied to the RoD-based similar formation stabilization problem, where the desired formation shape is expressed as a set of RoD constraints. Finally, numerical simulations are presented to illustrate the effectiveness of the theoretical results.